Pitfalls ; Living dangerously; Ang tunay na Amo - Lazaro, Cheche; Amo. (Quezon City Probe Productions, 1991)
Focuses on the violations of benguet Corporation in the reidents property and ecological rights; accidents in building constructions and factories and the Amo Band composed of young uncharacteristic band members who don't smoke, drink or take drugs but just play music for people who are fanatics to their music.
Pitfalls (20 min.) -- Living dangerously (18 min.) -- Ang tunay na Amo (17 min.)
VHS.
Keywords: Strip mining -- Philippines -- Benguet; Industrial accidents -- Philippines; Band musicians -- Philippines